Why We Derogate Victims and Demonize Perpetrators: the Influence of Just-World Beliefs and the Characteristics of Victims and Perpetrators - Mikani, Mehdi; Rafiee, Parisa (Social justice research, 2023)
Attempts to maintain a Belief in a Just World can sometimes lead to awry judgments about victims and perpetrators of violence. In a scenario-based study, we examined the associations of general belief in a just world with four BJW-maintenance strategies: victim blaming, victim derogation, perpetrator demonization, and compensation. We hypothesized that using a specific strategy depends on situational cues influencing the availability of that strategy and the level of a person’s BJW. More specifically, we tested whether BJW interacts with situational cues regarding the victim’s respectability and/or the perpetrator’s evilness, meaning that people with higher (vs. lower) BJW (a) tend to derogate the victim when the victim is presented as less (vs. more) respectable, (b) tend to demonize the perpetrator when the perpetrator is presented as more (vs. less) evil. Respectability (professor vs. car dealer) and evilness (with evilness cues vs. without evilness cues) were manipulated in a 2 × 2 between-subjects design. We also tested whether people use a single strategy versus multiple strategies to maintain their BJW. The results suggest that BJW-maintenance strategies are independent of one another, such that the availability or use of a particular strategy does not necessarily reduce or increase the use of other strategies. Taken together, our findings highlight the nuanced effects of just-world beliefs on how people react to and make sense of violent incidents.